Screening the antifungal activity of essential oils against decay fungi from palmyrah leaf handicrafts - Mahilrajan, Subajini (BioMed Central, 2014)
BACKGROUND: The whitish tender leaves of Palmyrah are used for making handicrafts. The problem with these articles is discolouration with time and become more brittle due to fungal attack. This could be prevented by some protective coating. Instead of expensive and harmful chemicals we decided to test natural plant essential oils to control fungal attack. Palmyrah leaf article decay fungi were isolated from two different sites of Jaffna peninsula. In this investigation Antifungal Activity of different plant essential oils from neem (Azadirachta indica), castor (Ricinus communis), citronella (Cymbopogon sp) and camphor (Cinnamomum camphora) obtained from local market have been evaluated against isolated fungi. For screening of Antifungal activity, tests and controls were set to determine minimum inhibitory concentration (MIC) and Percentage of Growth Inhibition. RESULTS: Morphologically three different types of Palmyrah leaf decay fungi were isolated and characterized as Aspergillus niger, Aspergillus flavus and Penicillium sp. Neem and castor oils have recorded no significant (0.05 > P) antifungal activity while citronella and camphor oils showed significantly different antifungal activity compared with control. Camphor oil and Citronella oil showed 100, 58.13% of average growth inhibition for A. niger. 96.38, 51.32% for A.flavus and 84.99, 72.76% for Penicillium sp respectively. Camphor oil showed highest percentage of growth inhibition at lowest minimum inhibitory concentration compared with citronella oil. Camphor oil was found to be highly antifungal and most effective against A niger, and A. flavus, compared with Penicillium sp and gave 100 percentage of growth inhibitions at 5, 1 and 15 ml/dl minimum inhibitory concentration respectively. CONCLUSION: Significantly higher broad-spectrum of antifungal activity was observed in camphor oil than other tested oils because it showed highest percentage of growth inhibition at lowest inhibitory concentration. Therefore it could be used for the development of new environmental friendly antifungal agent for the preservation of leafy handicrafts. Further formulation, field experiments are necessary to achieve this target.